2011
DOI: 10.1016/s1995-7645(11)60196-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of ethyl acetate extract of Bridelia micrantha for hepatoprotective and anti-oxidant activities on Wistar rats

Abstract: Results suggest that B. micrantha has hepatoprotective and anti oxidant potentials. However, further work involving fractionation needs to done to isolate the active compound responsible for the hepatoprotective activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Increase in the level of lipid peroxides in liver reflected the hepatocellular damage. The depletion of antioxidant defences and/or raise in free radical production deteriorates the prooxidant-antioxidant balance, leading to oxidative stress-induced cell death [46][47][48][49][50][51][52][53] . Depletion of GSH is known to result in enhanced lipid peroxidation and excessive lipid peroxidation can cause increased glutathione consumption [54] , as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in the level of lipid peroxides in liver reflected the hepatocellular damage. The depletion of antioxidant defences and/or raise in free radical production deteriorates the prooxidant-antioxidant balance, leading to oxidative stress-induced cell death [46][47][48][49][50][51][52][53] . Depletion of GSH is known to result in enhanced lipid peroxidation and excessive lipid peroxidation can cause increased glutathione consumption [54] , as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity experienced by liver during thioacetamide poisoning results from the production of metabolite, thioacetamide S-oxide, which is direct hepatotoxin. It has also been observed that thioacetamide causes changes in nucleolus and increased synthesis of guanine and cytosine rich RNA, with concomitant decrease in ribosomal RNA in the cytoplasm [18][19][20][21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds are also contribute to their inducing apoptosis by arresting cell cycle, regulating carcinogen metabolism and ontogenesis expression, inhibiting DNA binding and cell adhesion, migration, proliferation or differentiation, and blocking signalling pathways [28][29][30][31][32][33] . The hydrolysable tannin which is commonly found in the polar extract was previously reported to enhance the activity of the other phytochemicals by inhibition of the efflux mechanism, and decrease expression of P-glycoprotein, MRP1 and MRP2 membrane efflux transporter proteins in human cholangiocarcinoma [34] .…”
Section: Discussionmentioning
confidence: 99%